Water exchange for screening colonoscopy increases adenoma detection rate: a multicenter, double-blinded, randomized controlled trial - Cadoni, Sergio; Falt, Přemysl; Rondonotti, Emanuele; Radaelli, Franco; Fojtik, Petr; Gallittu, Paolo; Liggi, Mauro; Amato, Arnaldo; Paggi, Silvia; Smajstrla, Vit; Urban, Ondřej; Erriu, Matteo; et al. (Endoscopy, 2017)
Background and study aims Single-center studies, which were retrospective and/or involved unblinded colonoscopists, have suggested that water exchange, but not water immersion, compared with air insufflation significantly increases the adenoma detection rate (ADR), particularly in the proximal and right colon. Head-to-head comparison of the three techniques with ADR as primary outcome and blinded colonoscopists has not been reported to date. In a randomized controlled trial with blinded colonoscopists, we aimed to evaluate the impact of the three insertion techniques on ADR. Patients and methods A total of 1224 patients aged 50 - 70 years (672 males) and undergoing screening colonoscopy were randomized 1:1:1 to water exchange, water immersion, or air insufflation. Split-dose bowel preparation was adopted to optimize colon cleansing. After the cecum had been reached, a second colonoscopist who was blinded to the insertion technique performed the withdrawal. The primary outcome was overall ADR according to the three insertion techniques (water exchange, water immersion, and air insufflation). Secondary outcomes were other pertinent overall and right colon procedure-related measures. Results Baseline characteristics of the three groups were comparable. Compared with air insufflation, water exchange achieved a significantly higher overall ADR (49.3 %, 95 % confidence interval [CI] 44.3 % - 54.2 % vs. 40.4 % 95 %CI 35.6 % - 45.3 %; P = 0.03); water exchange showed comparable overall ADR vs. water immersion (43.4 %, 95 %CI 38.5 % - 48.3 %; P = 0.28). In the right colon, water exchange achieved a higher ADR than air insufflation (24.0 %, 95 %CI 20.0 % - 28.5 % vs. 16.9 %, 95 %CI 13.4 % - 20.9 %; P = 0.04) and a higher advanced ADR (6.1 %, 95 %CI 4.0 % - 9.0 % vs. 2.5 %, 95 %CI 1.2 % - 4.6 %; P = 0.03). Compared with air insufflation, the mean number of adenomas per procedure was significantly higher with water exchange (P = 0.04). Water exchange achieved the highest cleanliness scores (overall and in the right colon). These variables were comparable between water immersion and air insufflation. Conclusions The design with blinded observers strengthens the validity of the observation that water exchange, but not water immersion, can achieve significantly higher adenoma detection than air insufflation. Based on this evidence, the use of water exchange should be encouraged.Trial registered at ClinicalTrials.gov (NCT02041507).
Keywords: Colon, Ascending; senioři; vzduch; dvojitá slepá metoda; insuflace; Early Detection of Cancer; léčebná irigace; Double-Blind Method; voda; Middle Aged; mužské pohlaví; adenom; Water; Adenoma; Colonoscopy; časná detekce nádoru; nádory tračníku; ženské pohlaví; Cathartics; Humans; colon ascendens; Colonic Neoplasms; purgativa; Insufflation; lidé středního věku; colon transversum; Air; Female; Aged; Therapeutic Irrigation; Colon, Transverse; lidé; Male; kolonoskopie